Tubal monopolar electrocoagulation with section and excision as permanent surgical sterilization - Algara Urquiola, Luis (2015)
OBJETIVE: To determine the advantages of monopolar tubal electrocoagulation (ETM) as a method of surgical sterilization (EQ) permanent. MATERIALS AND METHODS: 141 patients who attended the consultation planning famiíiar Maternity Clinic Santa Ana, Venezuelan Institute of Social Security, during the period April 2003 to August 2004, that application was practiced a method of EQ voluntary permanent. They were grouped randomly into two groups, experimental one of 71 patients (50.4%), whom he underwent voluntary permanent EQ by ETM technique with removal section (ETMSR) and one of 70 patients (49.6%) who he underwent voluntary permanent EQ by conventional techniques. RESULTS: The mean age was 32 ± 6 years with 67.4% between 28 and 39 years. There was no significant difference in the number of deeds (average of 4 ± 2.3). EQ experimental technique was used in all women in the first group and in the control group Pomeroy 41.1%, 22.9% Madlener, Parkland 15.7%, 10% and Uchida Kroener 4.3%. 95% of patients remained hospilalizada (average of 2 ± 0.5 days). There were significant differences p <0.05 between study groups regarding pelvic pain -2.8% 12.9% experimental group and control-group, as in sex without fear of pregnancy, with 7.0% and 17.1%, respectively. The study cost savings of US $ 102.08 was noted for the experimental technique. CONCLUSION: The technique of ETMSR showed less postoperative pelvic pain, reduced fear of pregnancy on sex and lower cost than the traditional sterilization techniques.